A Yin‐Yang approach to education policy regarding health and the environment: early‐careerists' image of the future and priority programmes. (21st January 2016) - Watts, Paul; Custer, Benjamin; Yi, Zhuang‐Fang; Ontiri, Enoch; Pajaro, Marivic
Abstract: Since the inception of sustainable development (SD), there has been a somewhat ignored contradiction between paradigms that are ecosystem‐based and paradigms that are human‐based or purely economic. We suggest that this contradiction can be unified through a balance of the two. The Chinese Yin‐Yang philosophy is applied as a tool or approach to seeking balance between these ecocentric and anthropocentric paradigms. Priority education policy design for the merging of ecology and health are projected through an Ecohealth lens in response to increasing SD challenges and the intention of the international Ecohealth organization to contribute to SD goals. Meeting SD goals along the nexus of health and environment is further considered through early‐careerist cultural assessments and projections. The groups considered for their professional image of the future are: members of the Ecohealth Association Student Section and Chinese early‐careerists participating in a related conference. In response to SD goals, a problem‐based learning design is suggested as an education policy priority. Rather than approaching SD as a boolean concept, for example, by either focusing on ecosystem sustainability or economic development, we suggest education policy for programmes and curriculums that will help emerging professionals balance these paradigms, so as to best address national and global challenges.